Hematopoietic cell transplantation for older acute myeloid leukemia patients in first complete remission: results of a randomized phase III study : acute myeloid leukemia - Niederwieser, Dietger; Hasenclever, Dirk; Berdel, Wolfgang E.; Biemond, Barend Jacob; Al-Ali, Haifa Kathrin; Chalandon, Yves; Gelder, Michel van; Junghanß, Christian; Gahrton, Gösta; Hänel, Mathias; Hehlmann, Rüdiger; Heinicke, Thomas; et al. (Haematologica, 2025)
Given the selection of elderly patients with AML in first complete remission (CR1) the advantage of consolidation with allogeneic hematopoietic cell transplantation (HCT) over chemotherapy is still unclear. Newly diagnosed AML patients in CR1 aged 60-75 years were registered and a donor search initiated. After one consolidation cycle, patients with a matched donor were randomized to HCT with fludarabine/low-dose total body irradiation and cyclosporine/mycophenolate mofetil immunosuppression or conventional non-HCT. Primary outcome was restricted mean leukemia-free survival (RM-LFS) up to 5 years. Between 2010 and 2017, 245 patients (median age 67 years) were registered at CR1. After one consolidation, 26.9% of patients failed inclusion criteria. Of the 179 (73%) patients still on study, 75.4% had an HLA identical donor. Ten ineligible patients were excluded, and 125 randomized to HCT (N=83) or non-HCT (N=42). The primary outcome RM-LFS up to 5 years was 24.5 months (95% confidence interval [CI]: 18.9-30.1) in the HCT and 15.6 months (95% CI: 10.4-20.8) in the non-HCT arm (P=0.022) due to a decrease in cumulative relapse incidence from 91.1% (95% CI: 80.7-100.0) after non-HCT to 37.8% (95% CI: 27.2-48.4) after HCT (P<0.0001). The secondary endpoints RM-OS up to 5 years was 27.8 months (95% CI:22.3-33.2) in the HCT as compared to 28.6 months (95% CI: 22.2-35.0) in the non-HCT arm; non-relapse mortality at 5 years was 33.4% (95% CI: 23.0-43.9) with HCT and 0% without. In older patients with AML in CR1 5-year RM-LFS is better with HCT than with non-HCT consolidation treatment. The long-term RM-LFS benefit did not translate into a better RM-OS during the study period.
Online veröffentlicht: 8.8.2024
Gesehen am 31.07.2025